Digital Technology Innovation in Improving Financial Access for Low-Income Communities - Wanof, M. Indre (Technology and Society Perspectives (TACIT), 2023)
Access to finance is one of the key factors in building an inclusive and sustainable economy. Low-income communities often experience difficulties in accessing adequate financial services, such as savings, credit and insurance. This research aims to investigate how digital technology innovation has contributed to improving financial access for low-income people. This research is a literature analysis that utilises a qualitative approach. This approach involves analysing and interpreting data based on information and text taken from various sources. The study results show that digital technology innovation has opened up great opportunities in improving financial access for low-income people. Digital banking services, e-payments and alternative funding models have helped overcome traditional barriers, such as geographical distance and administrative costs, which often hinder access to financial services.